Preparation and application of self-piezoelectric aluminum nitride film / cavity assembly structure for promoting large-section critical bone defect repair

By fabricating a self-piezoelectric aluminum nitride thin film/cavity component structure, the biocompatibility and stability issues of traditional bone defect repair materials have been solved, achieving stable bioelectric signal output without external polarization and scaffolds, thus promoting efficient repair of bone defects.

CN120884744AActive Publication Date: 2025-11-04ZHUJIANG HOSPITAL OF SOUTHERN MEDICAL UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510885194.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-11-04
Estimated Expiration
2045-06-30

AI Technical Summary

Technical Problem

Existing bone defect repair materials suffer from problems such as a shortage of donor resources, insufficient bone integration capacity, and high treatment costs. Traditional piezoelectric materials have limitations in terms of biocompatibility, mechanical properties, and stability, and require external polarization or scaffold support, which affects their clinical application.

Method used

A self-piezoelectric aluminum nitride thin film/cavity component structure is adopted. The self-piezoelectric AlN thin film is prepared by photolithography and magnetron sputtering technology. Combined with silicon substrate thinning process, the cavity structure is optimized to enhance piezoelectric performance, so as to achieve stable bioelectric signal output without external polarization and scaffold.

Benefits of technology

It significantly improves piezoelectric properties, enabling it to autonomously output stable electrical signals in physiological environments, promoting osteoblast adhesion, proliferation and differentiation, and achieving significant bone regeneration of critical bone defects in rabbit femurs within 4 weeks, simplifying the bone repair process and improving clinical feasibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120884744A_ABST
    Figure CN120884744A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials and bone tissue engineering, and discloses preparation and application of a self-piezoelectric aluminum nitride film / cavity assembly structure for promoting large-section critical bone defect repair. The thin film is based on the piezoelectric property of AlN, the self-power-generation capacity in the physiological vibration environment is achieved by optimizing the cavity structure, and the surface current density of AlN is remarkably improved. The film provided by the invention can continuously provide stable bio-electricity signals under the conditions of no polarization treatment and no external physical stimulation, so that the adhesion, proliferation and differentiation of osteoblasts are promoted. In-vivo experiments show that the film / cavity assembly structure can effectively repair the critical bone defect of the rabbit femur without a stent, and is superior to an existing piezoelectric material. The limitation that a traditional piezoelectric bone repair material depends on external stimulation and a stent is broken through, and an innovative strategy with high clinical transformation potential is provided for bone tissue repair.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of bone tissue regeneration, and particularly relates to preparation and application of a self-piezoelectric aluminum nitride film / cavity assembly structure for promoting repair of large critical bone defects. BACKGROUND

[0002] Repair of bone defects has always been a major challenge in orthopedic clinics, especially critical size bone defects. Epidemiological data shows that there are about several million cases of bone defects worldwide each year, of which more than 1.5 million new bone defect patients are in China each year, of which about 15% are critical size bone defects. Due to the lack of sufficient bone regeneration capacity, if such bone defects are not repaired in time, it may lead to bone nonunion, limb deformity or loss of function, and seriously affect the quality of life of patients. At present, autologous bone transplantation, allogeneic bone transplantation and artificial bone materials are mainly used for treatment in clinics. Autologous bone transplantation is considered as the "gold standard", but its bone supply is insufficient, the incidence of complications in the donor area is as high as 20%-30%, and the surgical trauma is large, which limits its wide application. Although allogeneic bone transplantation avoids bone trauma, it has problems of immune rejection and bone resorption, and the long-term integration rate is less than 70%. In recent years, artificial synthetic bone materials have made some progress, and have excellent biocompatibility and plasticity, but their bone induction capacity and long-term mechanical properties are limited, especially the success rate in the repair of weight-bearing bone defects is only 60%-70%. In addition, emerging technologies such as stem cell transplantation and growth factor delivery have performed well in experimental studies, but due to their high cost and technical complexity, clinical promotion still faces challenges. Therefore, the current bone defect repair methods still have problems of lack of donor resources, insufficient bone integration capacity and high treatment cost, and the development of new, efficient and translatable bone repair materials has become the key to solving the difficulties of bone defect treatment.

[0003] Piezoelectric materials are widely used in bone tissue engineering due to their ability to generate electrical signals under mechanical stimulation. Studies have shown that bioelectric signals play a crucial role in bone regeneration, and the physiological load of the skeleton generates local potential differences, which in turn regulate the biological behavior of osteoblasts. However, most piezoelectric materials currently have the following problems: (1) Traditional inorganic piezoelectric materials (such as barium titanate and lead zirconate titanate) have high piezoelectric constants, but their chemical stability and biocompatibility are poor, making them difficult to use in biomedical fields; (2) Organic piezoelectric materials (such as polyvinylidene fluoride, PVDF) have good flexibility and biocompatibility, but their piezoelectric performance is low, and they must rely on external polarization or mechanical stretching to continuously output electrical signals; (3) Most existing piezoelectric bone repair materials need to be combined with scaffolds, making the application process complex and affecting their clinical feasibility. Therefore, developing a piezoelectric material that does not require external polarization or mechanical stimulation and can output long-term stable bioelectric signals without a scaffold is of great significance for bone defect repair.

[0004] Third-generation semiconductor materials (such as AlN, SiC, GaN) have attracted attention in high-frequency electronics, photodetection, 5G communication, and micro-electro-mechanical systems (MEMS) due to their wide bandgap, high breakdown electric field, excellent thermal stability, and mechanical properties. Compared to traditional piezoelectric materials (such as PZT and BaTiO3), third-generation semiconductor materials have higher chemical stability, better mechanical matching, and biocompatibility, making them suitable for biomedical sensing and implantable neural regulation. In the field of bone tissue regeneration, third-generation semiconductor materials have the potential to overcome the limitations of traditional piezoelectric materials. First, third-generation semiconductor materials have higher chemical stability and biocompatibility, avoiding the potential toxicity of harmful elements such as lead, making them more suitable for long-term implantation. Second, compared to organic piezoelectric materials (such as PVDF), third-generation semiconductor materials have superior piezoelectric properties and do not require polarization treatment or continuous external mechanical stretching to maintain stable bioelectric signal output. In addition, most traditional piezoelectric materials need to be combined with scaffolds, leading to material degradation and insufficient mechanical matching, while third-generation semiconductor materials have high mechanical strength and excellent structural stability, making them suitable for scaffold-free applications, simplifying the bone repair process, and improving clinical feasibility.

[0005] Therefore, third-generation semiconductor materials provide a more stable, efficient, and convenient new strategy for bone defect repair, and have the potential to become the next generation of bioelectric stimulation bone repair materials. SUMMARY

[0006] The purpose of the present application is to provide a self-piezoelectric aluminum nitride film / cavity assembly structure for promoting the repair of large critical bone defects and its application.

[0007] The application is realized by the technical scheme as follows:

[0008] A preparation method of a self-piezoelectric aluminum nitride film / cavity assembly structure for promoting repair of large-section critical bone defects, comprising the following steps:

[0009] S1, etching a shallow cavity structure of 3mm*10mm*2.5μm on a silicon (Si) substrate by using a photolithography process;

[0010] S2, continuing to use a magnetron sputtering technology to deposit a 1.0μm-thick piezoelectric aluminum nitride (AlN) layer;

[0011] S3, forming a cavity structure in the Si substrate by using a wet etching technology, and combining a silicon substrate thinning process to enhance the piezoelectric performance of the thin film, and finally obtaining a self-piezoelectric AlN film;

[0012] S4, attaching the prepared thin film to the surface of a titanium alloy cavity assembly by using PDMS, and forming a self-piezoelectric AlN film / cavity assembly structure after the PDMS solidifies.

[0013] Further, the etching in step S1 is wet etching, and the mask material used for etching is SiO2.

[0014] Further, the parameters during the magnetron sputtering in step S2 are as follows:

[0015] Target material: aluminum (99.9999%);

[0016] Substrate: Si (111);

[0017] Sputtering time: 710s;

[0018] Deposition rate: 76nm / min;

[0019] Nitrogen flow rate: 50sccm;

[0020] AC power: 7kW;

[0021] DC voltage: 15V;

[0022] Sputtering pressure: 0.2Pa.

[0023] Further, the etching solution used for the wet etching in step S3 is a 10% hydrofluoric acid solution, the etching is performed at room temperature, and the etching time is 40min.

[0024] Further, the size of the self-piezoelectric AlN film in step S3 is 5mm*10mm*0.1mm.

[0025] Use of a self-piezoelectric aluminum nitride thin film / cavity assembly structure in preparation of implants for treating large critical bone defects.

[0026] Compared with the prior art, the application has the following advantages:

[0027] 1. The core innovation of the self-piezoelectric AlN thin film / cavity assembly structure of the application lies in the cavity structure design of the self-piezoelectric AlN thin film, which significantly improves the current density on the surface of the AlN by precisely controlling the size of the cavity, thereby enhancing the piezoelectric performance and enabling the self-output of stable electrical signals in a physiological environment.

[0028] 2. Based on the piezoelectric properties of the AlN thin film, the self-power generation capability in a physiological vibration environment is realized by optimizing the cavity structure, and the surface current density of the AlN is significantly improved. The thin film of the application can continuously provide stable bioelectric signals without polarization treatment and external physical stimulation, thereby promoting the adhesion, proliferation and differentiation of osteoblasts. In vivo experiments show that the thin film / cavity assembly structure can effectively repair critical bone defects in the femur of rabbits without a scaffold, and achieve significant bone regeneration effect within 4 weeks, which is superior to existing piezoelectric materials. The application breaks through the limitations of traditional piezoelectric bone repair materials relying on external stimulation and scaffolds, and provides an innovative strategy with high clinical conversion potential for bone tissue repair. BRIEF DESCRIPTION OF DRAWINGS

[0029] Figure 1 It is a physical diagram of the AlN thin film;

[0030] Figure 2 It is a scanning electron microscope image of the cross section of the AlN thin film;

[0031] Figure 3 It is an electrical performance test diagram of the AlN thin film;

[0032] Figure 4 It is the cell proliferation result of r-BMSCs cells cultured on the surface of the AlN thin film for 24h, 48h and 72h;

[0033] Figure 5 It is the effect of the AlN thin film on promoting osteogenic proliferation and differentiation of BMSCs cells;

[0034] Figure 6 It is the effect of the AlN thin film / cavity assembly structure on promoting bone regeneration under critical bone defects;

[0035] Figure 7 It is a structural schematic diagram of the AlN thin film;

[0036] Figure 8 It is a schematic diagram of the AIN thin film / cavity assembly structure;

[0037] Figure 9Structure diagram of a seven-hole bone plate without AIN film;

[0038] Figure 10 Structure diagram of a seven-hole bone plate with AIN film;

[0039] Figure 11 Structure diagram of an eight-hole bone plate without AIN film;

[0040] Figure 12 Structure diagram of an eight-hole bone plate with AIN film;

[0041] In the figure: 1, AIN film; 2, cavity in the AIN film; 3, bolt of the cavity assembly; 4, bone plate; 5, hole position of the bone plate; 6, nut of the cavity assembly; 7, groove of the cavity assembly; 8, cavity in the cavity assembly; 9, groove of the bone plate. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solutions and advantages of the present application clearer and more apparent, the present application will be further described in detail below in combination with embodiments. The specific embodiments described herein are only used to explain the present application and do not limit the present application.

[0043] The experimental materials and equipment used in the following embodiments are commercially available unless otherwise specified. The experimental cells include:

[0044] rBMSCs cells: purchased from Sanyei (Guangzhou) Biotechnology Co., Ltd.

[0045] Example 1

[0046] Preparation and characterization of AlN film

[0047] S1, a shallow cavity structure with a depth of about 2.5 μm was etched on a silicon (Si) substrate using a photolithography process;

[0048] S2, a 1.0 μm thick AlN piezoelectric layer was deposited using a magnetron sputtering technique;

[0049] S3, a cavity structure was formed in the Si substrate using a wet etching technique, and a silicon substrate thinning process was combined to enhance the piezoelectric properties of the thin film, and finally a self-piezoelectric AlN film (size: 5mm*10mm*0.1mm) was obtained; as shown in the actual picture of the AlN film, the structural integrity and fine processing technology are exhibited. Figure 1

[0050] In order to characterize the micro-morphology and structural properties of the prepared thin film, the self-piezoelectric AlN film prepared in this embodiment was analyzed by scanning electron microscopy (SEM). Figure 2 ​The cross-section shows the AlN thin film structure, indicating that the multilayer structure of the thin film is complete and well combined.

[0051] To verify the electrical properties of the AlN thin film, the thin film was fixed on a Ti6Al4V bone plate, and the electrical properties were tested by simulating physiological motion frequency through a vibration platform. Figure 3 The results show that, compared with the group without the thin film, the introduction of the cavity in the AlN thin film and the cavity in the cavity assembly increases the piezoelectric performance by an order of magnitude. This indicates that the introduction of the cavity structure effectively optimizes the electrical response ability of the thin film and provides stable bioelectric signals for bone tissue repair.

[0052] Example 2

[0053] Preparation of AlN thin film / cavity assembly structure and bonding to bone plate

[0054] S1, the prepared AlN thin film 1 is attached to the surface of the titanium alloy cavity assembly with PDMS, and after the PDMS solidifies, a self-piezoelectric AlN thin film / cavity assembly structure is formed;

[0055] S2, as shown in Figures 9 to 12 , by embedding the AlN thin film / cavity assembly structure into the groove 9 of the bone plate, and combining the screw cap 6 of the cavity assembly in the cavity assembly with the screw 3 through the hole 5 of the bone plate, the AlN thin film / cavity assembly structure is fixed on the bone plate 4.

[0056] As shown in Figure 8 , the self-piezoelectric AlN thin film / cavity assembly structure of the application is composed of an AlN thin film 1, a cavity 2 in the AlN thin film, and a cavity 8 in the cavity assembly, wherein the AlN thin film 1 is attached to the groove 7 of the cavity assembly by PDMS.

[0057] Example 3

[0058] In vitro cell compatibility verification of AlN thin film and titanium alloy cavity assembly

[0059] To verify the biological safety of the self-piezoelectric AlN thin film prepared above, a cavity assembly group without a cavity, a cavity assembly without a cavity + vibration group, a thin film + cavity assembly without a cavity + vibration group, and a thin film / cavity assembly composite + vibration group are set up, the thin film and the cavity assembly sheet (the surface morphology is the same as the thin film, but there is no cavity and Mo electrode inside, and it cannot generate current) are attached to the bottom of a 12-well cell culture plate with polydimethylsiloxane (PDMS), and r-BMSCs are inoculated on the surface of the thin film for culture to evaluate its biocompatibility. By CCK-8 and live and dead staining Figure 4) The proliferation of r-BMSCs was detected after 24h, 48h and 72h of culture. The results showed that the cell proliferation ability of the film group had no significant difference with the control group, indicating that the AlN film and the cavity assembly had no obvious cytotoxicity.

[0060] Example 4

[0061] AlN film promotes the proliferation and differentiation of osteoblasts in vitro

[0062] The non-cavity assembly group, non-cavity assembly + vibration group, film + non-cavity assembly + vibration group and film / cavity assembly composite + vibration group were set up. The film and cavity assembly were attached to the bottom of the 6-well cell culture plate with PDMS, and then BMSCs were inoculated in the well plate. When the cell aggregation reached 70-80%, osteogenic induction medium was added for culture. Vibration intervention (0.5N, 1Hz, 10 minutes / day) was given to each well. After 7 days, alkaline phosphatase staining was performed, and after 21 days, alizarin red staining was performed to evaluate the effect of promoting the proliferation and differentiation of osteoblasts in vitro.

[0063] The detection results are shown in Figure 5 As can be seen from the figure, the AlN film under vibration can significantly promote the expression of alkaline phosphatase of osteoblasts and calcium deposition.

[0064] The non-cavity assembly group, non-cavity assembly + vibration group, film + non-cavity assembly + vibration group and film / cavity assembly composite + vibration group were set up. The film and cavity assembly were attached to the bottom of the 6-well cell culture plate with PDMS, and then BMSCs were inoculated in the well plate. When the cell aggregation reached 70-80%, osteogenic induction medium was added for culture. Vibration intervention (0.5N, 1Hz, 10 minutes / day) was given to each well. After 7 days, RNA was extracted, and the expression of BMP-2, Runx2 and Col-1a genes was detected.

[0065] The detection results are shown in Figure 5 As can be seen from the figure, the vibration of the self-piezoelectric film can significantly promote the expression of osteogenic related genes.

[0066] Example 5

[0067] The function of AlN film / cavity assembly structure in promoting the regeneration of large bone defect in vivo

[0068] The non-cavity assembly group, film + non-cavity assembly group and film / cavity assembly composite group were set up. We constructed a New Zealand rabbit femoral shaft critical bone defect model, and used AlN film / cavity assembly structure for internal fixation of femoral shaft bone defect. After 4 weeks of treatment, the material was taken out, and the imaging results were observed.

[0069] The results of animal experiments showed that there was almost no new bone growth in the defect site of the non-cavity component group. There was partial bone growth in the thin film + non-cavity component group, and there was a large amount of bone growth in the thin film / cavity component complex group, which was completely healed. Figure 6

[0070] In summary, the self-piezoelectric AlN thin film / cavity component complex prepared by the present application can significantly promote osteogenesis in vitro and be used for repairing critical bone defects in vivo, thereby treating large critical bone defects.

[0071] The above is only the preferred specific embodiment of the present application, but the protection scope of the present application is not limited thereto, any person skilled in the art can make equivalent replacement or change according to the technical scheme and the inventive concept of the present application within the technical range disclosed by the present application, which should be covered within the protection scope of the present application.​

Claims

1. A method for preparing a self-piezoelectric aluminum nitride thin film / cavity component structure that promotes the repair of large-segment critical bone defects, characterized in that, Includes the following steps: S1. A shallow cavity structure of 3mm*10mm*2.5μm is formed on a silicon substrate by photolithography. S2. Continue to use magnetron sputtering technology to deposit a 1.0 μm thick aluminum nitride piezoelectric layer; S3. A cavity structure is formed in the Si substrate using wet etching technology, combined with silicon substrate thinning process to enhance the piezoelectric properties of the film, and finally a self-piezoelectric AlN film is obtained. S4. The prepared film is attached to the surface of the titanium alloy cavity component using PDMS. After the PDMS solidifies, a self-piezoelectric AlN film / cavity component structure is formed.

2. The method for preparing a self-piezoelectric aluminum nitride thin film / cavity component structure for promoting the repair of large-segment critical bone defects according to claim 1, characterized in that, The etching described in step S1 is wet etching, and the mask material used for etching is SiO2.

3. The method for preparing a self-piezoelectric aluminum nitride thin film / cavity component structure for promoting the repair of large-segment critical bone defects according to claim 1, characterized in that, The parameters for magnetron sputtering described in step S2 are as follows: Target material: Aluminum (99.9999%); Substrate: Si(111); Splashing time: 710s; Deposition rate: 76 nm / min; Nitrogen flow rate: 50 sccm; AC power: 7kW; DC voltage: 15V; Sputtering pressure: 0.2 Pa.

4. The method for preparing a self-piezoelectric aluminum nitride thin film / cavity component structure for promoting the repair of large-segment critical bone defects according to claim 1, characterized in that, The wet etching process described in step S3 uses a 10% hydrofluoric acid solution, is performed at room temperature, and takes 40 minutes.

5. The method for preparing a self-piezoelectric aluminum nitride thin film / cavity component structure for promoting the repair of large-segment critical bone defects according to claim 1, characterized in that, The dimensions of the self-piezoelectric AlN film mentioned in step S3 are 5mm*10mm*0.1mm.

6. The self-piezoelectric aluminum nitride thin film / cavity assembly structure prepared by the method according to any one of claims 1 to 5.

7. The application of the self-piezoelectric aluminum nitride thin film / cavity assembly structure as described in claim 6 in the preparation of implants for treating large-segment critical bone defects.

Citation Information

Patent Citations

  • Oral cavity repairing film and preparation method thereof

    CN116407688A

  • Composite material for repairing critical large and small bone defects and preparation method thereof

    CN119015513A

  • Electrically conducting nanocomposite materials for biomedical applications

    US20030153965A1

  • Apparatus and method for characterizing adhesive bonding and osseointegration

    US20140150558A1

  • Aluminum nitride deposition using an AlN / Al sputter cycle technique

    US5232571A